Relationship Between Transactional Leadership and Employee Lifelong Learning with Prove Orientation as a Mediator - HSIEH, Ting-Hao; HO, Yu-Hsia; CHEN, Shieh-Liang (Journal of Research in Educational Sciences; Vol 10 No 1 (2019): JRES, Volume X, Issue 1(12), 2019DO - 10.14505//jres.v10.12.01, 2020)
The objective of this study was to investigate prove orientation mediate the relationship between transactional leadership and employee lifelong learning. For this, we distributed questionnaires to 800 employees, of which 512 valid questionnaires were received effectivity response rate of 64%. Confirmatory factor analysis and hierarchical regression analysis were employed to test our hypotheses. Our results suggested that transactional leadership positively influences employee lifelong learning, and that prove orientation has a mediating effect on this relationship. This manuscript provides a better understanding of employee lifelong learning can generate financial benefits for organizations. We conclude by proposing recommendations for management practices and future research.